The Influence Of The Think Talk Write (Ttw) Learning Model On Students' Critical Thinking Abilities Learning Fikih On Zakat Materials In Class Vii Mtss An-Nazmaiyah Kec. Sypispis - Saragih, Nurul Zahra; Daulai, Afrahul Fadhila; Miswar (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
This study aims to determine whether there is an influence of critical thinking skills of students taught using the Think Talk Write (TTW) learning model on the learning of Islamic jurisprudence on zakat material in class VII MTsS An-Nazmaiyah Kec. Sipispis. This type of research is quantitative research. With a total population of class VII students at MTsS An-Nazmaiyah Kec. Sipispis totaling 60 people. The sampling technique used in this study was simple random sampling, where sample members were taken from the population randomly without considering the strata in the population, so that the sample of this study was selected, namely students in class VII-A and VII-B. The research instruments used in this study were test validity, test reliability, question difficulty index, question discrimination power. The data analysis technique used in this study was the normality test, homogeneity test, hypothesis test. Data collection techniques were carried out using test and observation methods. The results of the research from the hypothesis test show that the Tcount value = 0.03 and Ttable = 1.70 indicate that 0.03 <1.70, thus Ho is rejected or Ha is accepted, so it can be concluded that there is a significant influence on the experimental class compared to the control class by using the Think Talk Write (TTW) learning model on Students' Critical Thinking Skills in Fiqh Learning of Zakat Material